Fundamentals of professional cooking and baking - Gonzalez, Gene R.; Sandique, Jill (Manila, Philippines : Anvil Publications, 2004)
The book is designed to evolve and grow with the growing standards of academe. It is meant to be revised and recipes would be added periodically to fit the changing requirements of the Food and Beverages Sectors.
Part I. Basics -- Part II. Recipes and Techniques -- Part III. Table Service.
Includes index.
Keywords: PROFESSIONAL COOKING